Pengaruh Kondisi Kerja, Kemampuan Kerja dan Kepemimpinan terhadap Kinerja Karyawan - Efawati, Yen (International Journal Administration, Business & Organization, 2020)
This research analyzes the effect of work conditions, workability, and leadership on employees’ performance. The issue of this research is raised because of the decrease in employees’ performance caused by several aspects such as uncomfortable work conditions, poor employees’ workabilities, and incompetent leadership. Based on those aspects mentioned, this research will discuss the way to increase employees’ performance. The proportional stratified random sampling is used for 72 respondents in the fashion industry at Bandung city. The data are analyzed using multiple linear regression analysis. This study shows that the level of workability and employees’ performance is closely related. Also, the relationship between leadership and employees’ performance is very strong. Moreover, the dominant factor that affects employees’ performance is the leadership aspect.